Caracterização transcriptômica de vias metabólicas na formiga Attini Atta sexdens rubropilosa Forel, 1908 (Hymenoptera, Formicidae) - Nascimento, Suzana Fortolan Baptista do [UNESP] (2015)
Mutualistic associations affect all living organisms. A useful biological model for studies of mutualism are Attini ants, whose nutrition depends on the association with basidiomycete fungi. These fungi produce depolymerases that act on degrading plant material, producing simple sugars that are essential for the survival of ants. Biochemical studies suggest that may be metabolic pathways, starting with steps catalyzed by fungal enzymes and ending with steps catalyzed by enzymes of the ants. Genomic studies indicate that the ants may not be able to synthesize some amino acids that would be supplied by the fungi, thus characterizing nutritional mutualistic dependence. To assess the extent of this metabolic dependence, in this thesis we aimed to annotate the transcriptome of Attine ant Atta sexdens rubropilosa in search of metabolic pathways. The presence and expression of genes from transcriptomics data of next generation sequencing were evaluated